Historical dictionary of Husserl's philosophy - Drummond, John J., 1945- (Historical dictionaries of religions, philosophies, and movements series, 2022)
"Historical Dictionary of Husserl's Philosophy, Second Edition contains a chronology, an introduction, and an extensive bibliography. The dictionary section has more than 600 cross-referenced entries on his key concepts and major writings as well as entries on his most important predecessors, contemporaries, and successors"--